BE KIND: Negotiating Ethical Proximities in Aotearoa/New Zealand during COVID‐19. (26th August 2021) - TRNKA, SUSANNA
ABSTRACT: Citizens do not merely respond to states of emergency; in democratic societies, they help constitute them. This essay analyzes New Zealanders' engagements in ethical reasoning during the country's first COVID‐19 lockdown. Specifically, I examine how we can understand a variety of public responses to emergency measures—including breaching regulations, threatening rule‐breakers, sealing off neighborhoods, and recasting citizen‐returnees as "strangers"—as negotiations of ethical proximities focused on keeping appropriately close that which is thought should be near, and keeping distanced that deemed best held afar.